Mothers, Men, and Child Protective Services Involvement - Berger, Lawrence M. (2009)
This study used data on 2,297 families from the Fragile Families and Child Wellbeing Study to examine whether Child Protective Services (CPS) involvement varies by maternal relationship status. Families were categorized according to whether the mother was living with a (male) partner or spouse, was involved in a dating relationship, or was not romantically involved. Families in which the mother was romantically involved were further delineated by whether her partner was the biological father of none, some, or all of the children in her household. Results indicated that families in which the mother was living with a man who was not the biological father of all children and those in which she was not romantically involved were significantly more likely to be contacted by CPS than those in which she was living with the biological father of all resident children. These findings withstood the inclusion of detailed controls for the mother’s characteristics and behaviors and (in two-parent families) her partner’s characteristics and behaviors, suggesting that they are not fully explained by observable social selection factors.